[Aerial View of Cal Poly] (1964)
View of Cal Poly and surrounding residences. Construction of Administration Building (001) is visible, North Mountain, red-brick dorms, Mott Gym, Dexter Library, Engineering East, Science, Poly Canyon, Poly "P" - looking east